2014
DOI: 10.1371/journal.pone.0095441
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium breve Attenuates Murine Dextran Sodium Sulfate-Induced Colitis and Increases Regulatory T Cell Responses

Abstract: While some probiotics have shown beneficial effects on preventing or treating colitis development, others have shown no effects. In this study, we have assessed the immunomodulating effects of two probiotic strains, Lactobacillus rhamnosus (L. rhamnosus) and Bifidobacterium breve (B. breve) on T cell polarization in vitro, using human peripheral blood mononuclear cells (PBMC), and in vivo, using murine dextran sodium sulfate (DSS) colitis model. With respect to the latter, the mRNA expression of T cell subset-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 55 publications
4
52
0
Order By: Relevance
“…In addition to clinical efficacy, we studied the effects of probiotic on systemic immune parameters, i.e. In animals fed with probiotics, local T cells have been shown to skew towards T regs in contrast to Th17 cells in response to antigens or subdue arthritis by inhibiting the Th1 response [33][34][35]. A 12-week probiotic therapy had no effect on these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical efficacy, we studied the effects of probiotic on systemic immune parameters, i.e. In animals fed with probiotics, local T cells have been shown to skew towards T regs in contrast to Th17 cells in response to antigens or subdue arthritis by inhibiting the Th1 response [33][34][35]. A 12-week probiotic therapy had no effect on these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Immune disorder is supposed to be one of the main pathogenic mechanisms of autoimmune diseases, such as IBD [82] and rheumatoid arthritis (RA) [83] . Probiotics modulate the host-pathogen interactions by effecting on the innate immune responses, which involve the TLR, NF-ÎșB, MAPK, and c-Jun NH2-terminal kinase (JNK) pathways.…”
Section: Molecular Mechanisms Of Probiotics In Gi Diseasesmentioning
confidence: 99%
“…In an IBD-like model, B. breve NutRes 204 ameliorated dextran sodium sulfate (DSS)-induced colitis. This was linked to increases in Tregs and decreases in Th17 (CD4 + IL-17 + ) cell subsets in Peyer's patches of DSS-treated mice and concurrent differential expression of Th1 cells, Th2, and Treg-associated cytokines [51]. Zuo et al reported an increase in mesenteric lymph node (MLN) Tregs (i.e.…”
Section: T Cellsmentioning
confidence: 99%
“…emphasise the importance of the species and even the strain of Bifidobacterium that is used. In a necrotising enterocolitis (NEC, which is also linked to epithelial barrier disruption) mouse model, B. breve was shown to up-regulate TJ proteins Claudin 4 and Occludin [51], and a non-specified species of Bifidobacterium increased ZO-1 in a rat NEC model [8]. Studies have also shown that the effects of bifidobacteria are only exerted, or are increased, when live bifidobacteria are used.…”
Section: Epithelial Cellsmentioning
confidence: 99%